PENGARUH OVERALL SHOPPING TRIP GOAL DAN STORE SPESIFIC GOALS TERHADAP UNPLANNED BUYING PADA HYPERMART SUPERMALL PAKUWON INDAH SURABAYA - RIANTHY, GOEY (Kajian Ilmiah Mahasiswa Manajemen, 2012)
The purpose of this study is to investigate the influnces of overall shopping trip goal and store spesific goals to unplanned buying in Hypermart Supermall Pakuwon Indah Surabaya and differences in propensity to unplanned buying by using the control variable consumer demographics. This study uses primary data obtained directly by involving 150 respondents as a research subject.The criteria for the sample used in this study were aged at least 17 years, respondents living in Surabaya and the respondent had ever shopped at least 2 times in Hypermart Supermall Pakuwon Indah Surabaya.Multiple linear regression analysis techniques are used to test the influence of overall shopping trip goal and store spesific goals to unplanned buying.ANOVA and T-test was used to test differences in unplanned buying based on variable consumer demographics. ANOVA was used to examine differences in unplanned buying by age and income, while different t-test was used to examine differences in unplanned buying by gender and education. The results of this study indicate that out of store factors that includes overall shopping trip goal and store specific goals significantly influence unplanned buying. Additional results in this study, for different t-test showed no difference in unplanned purchases on review of the sexes and for no perberbedaan ANOVA by age, income and education.